Tidal turbines in the estuarine environment: From identifying optimal location to environmental impact. (May 2021) - Ross, Lauren; Sottolichio, Aldo; Huybrechts, Nicolas; Brunet, Pascal
Abstract: Estuaries that feature large tidal ranges (macrotidal) have recently received attention for their potential to generate energy by tidal stream turbines. As estuaries are delicate ecosystems and often have large human populations residing on their shores, determining where to place the turbines and how they will impact the hydrodynamics and sediment transport of these systems is vital to their successful implementation. The aim of this study is to provide a framework for assessing an estuary for turbine placement, including determining how the turbines will impact the environment (focusing on the physics), and examining other items that could peripherally affect the tidal turbine farm location or impact. This work was carried out using the Gironde Estuary as a case study and included a combination of in-situ data collection and numerical modeling. In terms of the turbine farm impact on the hydrodynamics and Suspended Sediment Concentration (SSC), results showed that the inclusion of a farm reduced currents up to 10% and decreased SSC up to 15 mg/l. The decrease in SSC was due to the attenuated current velocities decreasing friction velocity and thus near bottom generated turbulence that suspends bottom sediment. Over time, the decreased SSC will lead to sediment accumulation and new bottom features. Highlights: Framework established for assessing an estuary for turbine placement and environmental impacts. Turbines decreased current velocities and suspended sediment concentration in the near and far field from turbine locations. Decreased suspended sediment concentration due to decreased friction velocity and near bottom turbulence production.